Digital Innovation or Traditional Methods: Stakeholder Preferences for Digitalizing Public Complaints in Pekanbaru City, Indonesia - Handrian, Eko; Ekha Putera, Roni; Asrinaldi, Asrinaldi; Zetra, Aidinil (Indonesian Association for Public Administration (IAPA), 2024)
This research explores internal stakeholders' preferences for the use of digital public complaint applications compared to traditional communication methods such as telephone in public services in Pekanbaru City. Using a qualitative approach, the case study method on the Pekan Kita Application (PEKA) was chosen to analyze in depth stakeholder preferences for the adoption of digital innovation. Data was collected through semi-structured interviews, participant observation and documentation. The findings show that the adoption of the PEKA application is more symbolic, where stakeholders prefer conventional methods because they are considered more practical and in accordance with daily work habits. This indicates that there is a gap between the digital innovation policies implemented and the real needs and preferences of internal stakeholders. The need for fast response and responsiveness to emergency conditions is a preference for internal stakeholders in digital public complaints policies. The implications of this research are very important in designing more effective and humane digital policies, which do not only focus on technical aspects, but also consider non-technical factors such as habits, needs, preferences of internal users and humanity so that technology implementation can be more successful and relevant in practice.